Tracking prediction to avoid obstacle path of agricultural unmanned aerial vehicle based on particle filter. (April 2018) - Zhang, Xihai; Fan, Chengguo; Fang, Junlong; Xu, Suijia; Du, Jiali
In this article, aiming at the track prediction to avoid obstacles of the plant-protecting unmanned aerial vehicle, first the track points of the curvature variation of non-uniform distribution according to the characters of the track curvature to avoid obstacles were calculated, and the wind model at the low altitude was built. Then, a tracking prediction method of unmanned aerial vehicle was proposed based on the algorithm of particle filter under the situation of uncertain disturbances. Finally, the track to avoid obstacles was divided into curved track and linear track using the bricks mechanism and the tracking prediction was done. The simulated result shows that proposed method can achieve the tracking prediction better with less smaller and better robustness when there are uncertain Gaussian noise, wind speed below 2 m/s as well as error and random noise of the sensor existing.